CONTRIBUTION OF INFORMATION AND COMMUNICATION TECHNOLOGIES (ICTs) IN THE TEACHING-LEARNING PROCESS - Silva, Milian Pereira Santana; Holzach, Juliana Cristina [UNESP]; Castro, Douglas Azevedo (Fundacao Univ Tocantins, 2023)
This literature review investigates the contribution of Information and Communication Technologies (ICTs) in the teaching-learning process through educational software. With the rapid advancement of ICTs, the educational landscape has undergone significant transformations, offering new opportunities to improve the quality of education. Educational software, specifically designed to support teaching and learning processes, has played an important role in this transformation. The study examines how educational software, driven by ICTs, has influenced teaching and learning at different levels of education, from elementary school to higher education. Technological resources provide interactive resources, simulations, educational games and other tools that promote the active participation of students, stimulating interest and motivation to learn. In short, ICTs and educational software have the potential to transform the teaching -learning process, offering new possibilities and improving the educational experience.
Keywords: Learning; Technology; Softwares; Education